VD_FINDINFO ML / 2019 / 247 vom 30. Dezember 2019 - VD Tribunal cantonal (2019)
DÉPENS, PRIMAUTÉ DU DROIT FÉDÉRAL, AVOCAT | 49 al. 1 Cst., 80 al. 1 LP, 47 LPAv, 111 al. 2 CPC (CH), 95 al. 1 let. b CPC (CH)